2017
DOI: 10.1016/j.yebeh.2017.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Dravet syndrome: Characteristics, comorbidities, and caregiver concerns

Abstract: The Dravet Syndrome Foundation (DSF) conducted the largest in-depth survey of parents and caregivers of patients with Dravet syndrome (DS) to date, in order to (1) identify top concerns among caregivers, (2) establish an approximate frequency of characteristics and comorbidities of DS beyond seizures, and (3) provide direction for clinicians and researchers looking to study the effects of DS on the patient and family unit. Two hundred fifty-six responses were received representing a patient age range of 9month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
169
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(196 citation statements)
references
References 22 publications
18
169
2
4
Order By: Relevance
“…[18] Long term studies on patients with DS show that very few individuals live independently [25], and this survey found that relatively few adult patients with DS receive help for independent living. The emotional impact on parents in the DISCUSS cohort is similar to those reported by families caring for a child with DS, other rare diseases and childhood epilepsies in general [3,11,[26][27][28]. Future research to systematically identify the most important caregiver domains that are impacted by caring for a child with DS would be useful to obtain a quantitative measure to enable comparison to other groups of carers and the public and understand the true impact of DS on caregivers' lives [4].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…[18] Long term studies on patients with DS show that very few individuals live independently [25], and this survey found that relatively few adult patients with DS receive help for independent living. The emotional impact on parents in the DISCUSS cohort is similar to those reported by families caring for a child with DS, other rare diseases and childhood epilepsies in general [3,11,[26][27][28]. Future research to systematically identify the most important caregiver domains that are impacted by caring for a child with DS would be useful to obtain a quantitative measure to enable comparison to other groups of carers and the public and understand the true impact of DS on caregivers' lives [4].…”
Section: Discussionmentioning
confidence: 57%
“…A recent international survey reported that caregivers of patients with DS contend with a wide range of other effects of the disease, with speech/ communication, impacts on siblings and cognitive impairment ranking as their top concern. [11] Nearly two-thirds of caregivers were reported as having suffered from depression [11].…”
Section: Introductionmentioning
confidence: 99%
“…In an open response survey conducted by Villas et al nearly two‐thirds of DS caregivers have depressive symptoms according to the author's interpretation, which has also been confirmed in the results of the German DS study, with 23%, 16%, and 8% of caregivers reporting mild, moderate, and severe depressive symptoms, respectively . These detailed psychometric data have been provided in a more granular format than ever before, assessing the severity of pediatric caregiver depressive symptoms using the BDI‐II instrument.…”
Section: Discussionmentioning
confidence: 59%
“…2,3 Autism spectrum disorder (ASD) features have been reported in patients with DS but were defined as « autistic traits » without using standardized tools. 6,18,19,24 Neophobia, 6,19 adherence to routines and sensory particularities, are less described. 4,6,[16][17][18][19][20] Most studies have reported lack of verbal communication, with 10%-79% of patients showing social problems, such as poor peer relationships, being withdrawn, lack of emotional reciprocity, social rules problems, or excessive familiarity.…”
Section: Introductionmentioning
confidence: 99%
“…6,18,19,[21][22][23] Restricted and unusual interests, like obsessions, perseverations, or self-stimulations, are reported in 24%-69%. 6,18,19,24 Neophobia, 6,19 adherence to routines and sensory particularities, are less described. 18,25 Only one study assessed ASD in children with DS using standardized tools: Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV-TR) and the International Classification of Diseases, Tenth Revision (ICD-10) criteria, the Childhood Autism Rating Scale (CARS) diagnosis tool, and the Autism Behavior Checklist (ABC), 6 but without any gold standard diagnosis tool (Autism Diagnostic Interview-Revised [ADI-R] or Autism Diagnostic Observation Schedule, Second Edition ).…”
Section: Introductionmentioning
confidence: 99%